Diurnal changes in antioxidant and carotenoid composition in the Mediterranean schlerophyll tree Quercus ilex(L) during winter - García-Plazaola, J. I.; Artetxe, Unai; BECERRIL, J. M.; Garcı, Ignacio (Plant Science, 1999)
Seasonal changes of pigment composition and antioxidant content were characterized in the Mediterranean evergreen holm oak (Quercus ilex L.). Higher contents of antioxidants and carotenoids, with a photoprotective role during winter, indicated that this period was highly stressful, so a study of diurnal changes in photosynthesis, pigments and carotenoids was conducted during January in sun and shade leaves. Sun and shade leaves were used to compare the effects due only to low temperature separate from those resulting from the interaction of light. During winter, a relatively high rate of CO2 ﬁxation on sun leaves represented an important sink for photosynthetic electrons contributing to the annual carbon balance of the plant. This high rate contrasted with a reduced Fv :Fm, even at predawn. This reduction was correlated with the accumulation of zeaxanthin at the expense of violaxanthin by de-epoxidation. Sun leaves were also protected by a higher concentration of antioxidants (ascorbate, glutathione and tocopherol) and carotenoids (except lutein epoxide). Ascorbate was 10–50-fold greater than the other antioxidants, indicating a central role in protection against photooxidative stress. Nevertheless those mechanisms were unable to avoid a loss of hydrophilic antioxidants (glutathione and ascorbate) and xanthophylls during the initial morning hours after dawn, indicating that the ﬁrst target of photooxidative damage was these molecules
Keywords: Holm oak; low-temperature stress; Mediterranean evergreens; photoinhibition; photoprotection; xanthophyll cycle

Diurnal changes in antioxidant and carotenoid composition in the Mediterranean schlerophyll tree Quercus ilex(L) during winter (Plant Science, 1999)
Seasonal changes of pigment composition and antioxidant content were characterized in the Mediterranean evergreen holm oak (Quercus ilex L.). Higher contents of antioxidants and carotenoids, with a photoprotective role during winter, indicated that this period was highly stressful, so a study of diurnal changes in photosynthesis, pigments and carotenoids was conducted during January in sun and shade leaves. Sun and shade leaves were used to compare the effects due only to low temperature separate from those resulting from the interaction of light. During winter, a relatively high rate of CO2 ﬁxation on sun leaves represented an important sink for photosynthetic electrons contributing to the annual carbon balance of the plant. This high rate contrasted with a reduced Fv :Fm, even at predawn. This reduction was correlated with the accumulation of zeaxanthin at the expense of violaxanthin by de-epoxidation. Sun leaves were also protected by a higher concentration of antioxidants (ascorbate, glutathione and tocopherol) and carotenoids (except lutein epoxide). Ascorbate was 10–50-fold greater than the other antioxidants, indicating a central role in protection against photooxidative stress. Nevertheless those mechanisms were unable to avoid a loss of hydrophilic antioxidants (glutathione and ascorbate) and xanthophylls during the initial morning hours after dawn, indicating that the ﬁrst target of photooxidative damage was these molecules